2023
DOI: 10.1002/solr.202200932
|View full text |Cite
|
Sign up to set email alerts
|

Stacking Interactions and Photovoltaic Performance of Cs2AgBiBr6 Perovskite

Abstract: Elpasolite Cs2AgBiBr6 also known as double perovskite has been touted in recent years as a promising alternative to the lead‐based perovskite for light harvesting. Its structure and properties mainly stem from the replacement of Pb2+ cation with a pair of aliovalent silver (Ag+) and bismuth (Bi3+) cations. Although the elpasolite Cs2AgBiBr6 exhibits improved stability, its photophysical properties and device performance are inferior to those of the Pb‐based perovskites. To date, numerous efforts have been gear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 209 publications
0
4
0
1
Order By: Relevance
“…The inherent constraints have significantly limited their practical applications. [39][40][41][42] The interesting matters of stability have attracted greater attention and have been partially overcome through the substitution of the organic cation with inorganic cesium ions. This development has inspired the scientific community to begin a search for metal halide perovskite compounds that possess similar photoelectric characteristics while simultaneously exhibiting non-toxicity and steadfastness.…”
Section: Introductionmentioning
confidence: 99%
“…The inherent constraints have significantly limited their practical applications. [39][40][41][42] The interesting matters of stability have attracted greater attention and have been partially overcome through the substitution of the organic cation with inorganic cesium ions. This development has inspired the scientific community to begin a search for metal halide perovskite compounds that possess similar photoelectric characteristics while simultaneously exhibiting non-toxicity and steadfastness.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Cs 2 AgBiBr 6 has gathered considerable attention among double perovskites due to its high ambient stability and nontoxicity. [10][11][12] However, the PCE of the Cs 2 AgBiBr 6 -based PSCs has lagged behind traditional organicinorganic Pb-based PSCs. Studies to date have shown that the performance limiting factor of these cells is the large indirect bandgap of Cs 2 AgBiBr 6 (1.9-2.2 eV), using unsuitable charge transporting layers, strong electron-phonon coupling, and poor film quality.…”
Section: Introductionmentioning
confidence: 99%
“…A highly stable double perovskite class of a Cs 2 AgBiBr 6 absorber layer has recently been reported as a viable substitute for Pb-based perovskite. As a result, Cs 2 AgBi 0.75 Sb 0.25 Br 6 is favored for this study due to its various benefits, including being lead-free, non-toxic, extremely stable, and compatible with a variety of transport layers, as reported in the literature [10][11][12].…”
Section: Introductionmentioning
confidence: 99%